High temperature corrosion of commercial FeCrAl alloys (Kanthal AF) in nitrogen gas - Veskovič-Bukudura S.; Kovač J.; Karpe B.; Umek P.; Nagode A.; Cerc-Korošec R.; Bizjak M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present study, the corrosion mechanism of commercial FeCrAl alloy (Kanthal AF) during annealing in nitrogen gas (4.6) at 900°C and 1200°C is outlined. Isothermal and thermo-cyclic tests with varying total exposure times, heating rates, and annealing temperatures were performed. Oxidation test in air and nitrogen gas were carried out by thermogravimetric analysis. The microstructure is characterized by scanning electron microscopy (SEM-EDX), Auger electron spectroscopy (AES), and focused ion beam (FIB-EDX) analysis. The results show that the progression of corrosion takes place through the formation of localized subsurface nitridation regions, composed of AlN phase particles, which reduces the aluminum activity and causes embrittlement and spallation. The processes of Al-nitride formation and Al-oxide scale growth depend on annealing temperature and heating rate. It was found that nitridation of the FeCrAl alloy is a faster process than oxidation during annealing in a nitrogen gas with low oxygen partial pressure and represents the main cause of alloy degradation.